Estudo histológico e parasitológico do trato gastrintestinal de cães infectados com Leishmania (Leishmania) chagasi - Aldair Junio Woyames Pinto (2011)
There are few descriptions of parasitological and pathological changes related to the involvement of the gastrointestinal tract (TGI) and canine visceral leishmaniasis (CVL), especially considering the TGI systematically. Thus, the aim of this work was investigated and correlated, physical clinical evaluation and TGI parasitological data of naturally infected dogs with Leishmania (Leishmania) chagasi from the metropolitan region of Belo Horizonte, MG. After serological (IFAT and ELISA) and parasitological (bone marrow smear) positive results for L. chagasi, the animals were clinically classified into two groups: symptomatic dogs (n = 6) when at least one clinical alteration suggestive of CVL had been observed, asymptomatic dogs (n = 6) when was not observed clinical alteration. Another group, formed by uninfected dogs was included as control group (n = 3). The animals were euthanized and the samples of TGI: esophagus, stomach, duodenum, jejunum, ileum, cecum, colon and rectum were collected and fixed in formalin 10%, then embedded in paraffin, and solution Carnoy's under refrigeration (4 ° C ) embedded in glycol methacrylate resin (GMA). TGI samples were evaluated by immunohistochemistry assay and staining assy (H&E, Toluidine blue, PAS and Dominici). Dry seborrhea and onychogryphosis changes were seen in greater proportion. The infected animals showed an inflammatory cells increase in the TGI lamina propria and submucosa (except the esophagus) compared with control animals. Mononuclear cells were found, manly plasma cells, macrophages and lymphocytes. Macrophages could be seen with peculiar morphology, with parasite visualization of the or the presence of vacuoles inside the immunohistochemical staining technique described by Tafuri et al., 2004 immunoperoxidase showed satisfactory results when used throughout the GI tract. During the evaluation it was observed that the regions of positive marking, amastigotes have easily located in the segments of the lamina propria and submucosa of the GI tract. Markings of amastigotes were found in 88.8% higher proportion underlying muscularis mucosae at the base of the lamina propria. Of the six positive animals where the markings were also located in the anterior portions of the GI tract (stomach, duodenum and ileum) 100% of amastigotes were found in greater proportion close to the lumen, within the villi of the intestinal epithelium below. In fact, the most infested areas were morphometrically the region of the duodenum followed by the cecum groups asymptomatic, the symptomatic group. Regions of the colon, rectum, stomach and ileum also showed positive markings. There were no markings of amastigotes of the parasite in the esophagus and jejunum of infected dogs. The technique of embedding in GMA fabric dog proved to be of great importance for the evaluation of the experiment, with a best result for the evaluation techniques used when routine histology compared with paraffin wax. There was statistical difference in the evaluation of mast cells in the esophagus, jejunum, ileum, cecum and colon. The use of the inclusion of biological material (TGI dog) in methacrylate plastic resin, showed satisfactory results for routine histology stains, standardized according to our project. The LVC has several clinical signs, the changes being considered common dermatological disease. However changes in clinical TGI are not easily found despite the presence of the parasite is commonly found in the same.